2011
DOI: 10.1007/s00268-011-1296-z
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Results of Surgery for Small Intestinal Neuroendocrine Tumors at a Tertiary Referral Center

Abstract: For the first time, m.lgllm and da.lgllm, LTL, PC, and EAM are demonstrated to be independent prognostic factors by multivariate analysis. Locoregional removal of the PT/m.lgllm. was a positive prognostic factor by crude and adjusted analysis and may influence survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
229
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(242 citation statements)
references
References 59 publications
10
229
1
2
Order By: Relevance
“…Most SBNETs are low-grade lesions; nevertheless, up to 90% of patients with SBNET have lymph node metastases, and in 45-70% of cases, liver metastases are present at the initial diagnosis , Norlén et al 2012, Miller et al 2014. These intriguing characteristics contribute to a 5-year survival of less than 60% from diagnosis of liver metastases (Ahmed et al 2009) compared to about 80% in patients with loco-regionally limited disease (Norlén et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most SBNETs are low-grade lesions; nevertheless, up to 90% of patients with SBNET have lymph node metastases, and in 45-70% of cases, liver metastases are present at the initial diagnosis , Norlén et al 2012, Miller et al 2014. These intriguing characteristics contribute to a 5-year survival of less than 60% from diagnosis of liver metastases (Ahmed et al 2009) compared to about 80% in patients with loco-regionally limited disease (Norlén et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These intriguing characteristics contribute to a 5-year survival of less than 60% from diagnosis of liver metastases (Ahmed et al 2009) compared to about 80% in patients with loco-regionally limited disease (Norlén et al 2012). The lack of specific and sensitive biomarkers to stratify NETs according to subtype, determine tumour burden, assess disease progression, select patients for individualised treatment and monitor treatment efficacy is a key issue in management of NETs (Modlin et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Optimal lymphadenectomy may be really challenging, especially when there is coexistence of mesenteric fibrosis or large lymph node metastases of the superior mesenteric artery (SMA) (21). Optimal enterectomy with optimal lymphadenectomy is vital for improving survival and preventing recurrence (6,20,22). Therefore, it is advisable that such operations be conducted at specialized centers with relevant expertise treating a large number of patients.…”
Section: Locoregional Enterectomy With Lymph Node Dissectionmentioning
confidence: 99%
“…Most patients with si-NENs have prolonged survival due to the low NEN cell proliferative rate and, thus, patients with localized disease have a 5-year overall survival (OS) rate of 70-100%, whereas for those with distant metastases, more common in the liver, it is 35-60% (6). In autopsy studies, the reported incidence of si-NENs is high (8,34/100,000), indicating that their true incidence may be higher than suspected, since many will remain undiagnosed due to lack of clinical manifestations (7).…”
mentioning
confidence: 99%
“…However, many centres of excellence in nets have developed an aggressive surgical approach for these patients. Retrospective data have demonstrated improved survival in patients undergoing resection of the mesenteric disease compared with patients that did not (median survival: 11 years vs. 2.6 years) [37][38][39] . The suggestion is that resection of regional disease delayed onset of the obstruction and ischemia frequently seen in later stages of the disease.…”
Section: Summary Of Evidencementioning
confidence: 99%